Priority analysis of pre-investment risks. Issue 1 (1st January 2020) - Hosein, Gino; Ray, Indrajit
Abstract: Residential building construction projects are common to the local construction industry and they are almost always behind the schedule because of unforeseen risks. In the pre-investment phase, risks are high because of the uncertainty of the scope of works; therefore, a risk assessment report is even more important. This results in risks being scored incorrectly and some not being identified. The purpose of this research is to assist investors and other decision makers in identifying with specific risks in the pre-investment stage. Surveying of a sample population of construction professionals was carried out to determine the risk parameter scores based on a risk scoring matrix. The risk parameter scores were then prioritized in the order of highest to lowest risk impacts. Data analysis of the results was achieved by statistical tests. The results were then validated through case studies. This research finalized the priority of the risk parameters and identified that the major risk parameters are availability of direct labour, engineering designs, availability of materials, project scheduling and project management, respectively. Statistical tests confirmed that the specific differences between the dependent variables were cost and quality.